With-without Privilege Funds: Allocative Efficiency and Local Growth Welfare - Priyadi, Unggul; Shidiqie, Jannahar Saddam Ash; E. H., Lak Lak Nazhat; Nordin, Shahrina Md; Imron, Mochamad Ali (International Journal of Economics and Financial Issues, 2021)
Regional local income is input in the local economic development. The sectors are local own-source income, fiscal balance transfers from the central government to regions, privilege funds of Yogyakarta and the other local incomes, those are used by the government as capital to raise local economic development to be better. So, this study to analyze the efficiency of local income of cities in Yogyakarta Province. One of results of this study describe that one of cities in the Yogyakarta is inefficient without the privilege fund inputs, but the effect of the allocation of privilege funds is very good for economic development and improving prosperous of societies. Generally, the privilege funds of Yogyakarta can be able to support the local growth welfare and prosperous of societies as output efficienly 100% based on the data envelopment analysis method. Keywords: Privilege Funds, Local Growth Welfare, Data Envelopment Analysis JEL Classifications: G2, H6, O1, I3 DOI: https://doi.org/10.32479/ijefi.8884